The Adoption Model of Technological Innovations That Have an Impact on the Welfare of the Community in the Village of Koto Masjid, Riau Province - Adianto; Resa Vio Vani (International Journal of Social Science and Business, 2022)
This research examines the adoption of technological innovations in the field of fisheries that have successfully contributed to the improvement and change of livelihoods for the community. This study aims to analyze in-depth and comprehensively to construct a model for the adoption of technological innovations that takes place and can contribute to the welfare of society. The method used in this study is a qualitative research paradigm with a case study approach being the choice of researchers in conducting research with the theme of innovation adoption. The results of this study found that the adoption model of technological innovation in the field of fisheries in the Minapolitan area of Koto Mesjid Village, Riau Province, Indonesia turned out to have contributed to the improvement and change of livelihoods for the community. The success of the community in adopting technological innovations in the field of fisheries has gradually improved the economic conditions of the community. The construction of the technological innovation adoption model is arranged to start from the existence of local values as a link in the adoption process, the existence of proof and promises of benefits (rewards) in the process, the existence of regional characteristics, community, and supporting personal variables, the existence of factors that can be a stimulus for the community to be able to accept technological innovations in the field of fisheries and have a clear decision-making flow.